Measuring vital capacity in amyotrophic lateral sclerosis: Effects of interfaces and reproducibility. (January 2021) - Pellegrino, Giulia Michela; Sferrazza Papa, Giuseppe Francesco; Centanni, Stefano; Corbo, Massimo; Kvarnberg, David; Tobin, Martin J.; Laghi, Franco
Abstract: Background: Deterioration of vital capacity (VC) in amyotrophic lateral sclerosis (ALS) signifies disease progression and indicates need for non-invasive ventilation. Weak facial muscles consequent to ALS, with resulting poor mouth seal, may interfere with the accuracy of VC measurements. Objectives: To determine whether different interfaces affect VC measurements in ALS patients and whether the interface yielding the largest VC produces an even higher VC when re-measured after one week (learning effect). To explore the relationship between optimal interface VC and sniff nasal pressure (SNIP), a measurement of global inspiratory muscle strength. Methods: Thirty-five patients (17 bulbar and 18 spinal ALS) were studied. Three interfaces (rigid-cylindrical, flanged, oronasal mask) were tested. One week after the first visit, VC was recorded using the optimal interface. SNIP recordings were also obtained. Results: In the bulbar ALS group, median (interquartile range) VC with the flanged mouthpiece was 8.4% (3.9–15.5) larger than with the cylindrical mouthpiece (p < 0.001). VC values with oronasal mask were intermediate to VC with the other two interfaces. In spinal ALS, flanged mouthpiece VC was 4.6% (2.3–7.5) larger than with oronasal mask (p < 0.0006). The latter was 4.5% (0.6–5.2) smaller than with the cylindrical mouthpiece (p = 0.002). In both groups, VC during the second visit was greater than during the first visit (p < 0.025). SNIPs were logarithmically related to VC values recorded with the flanged mouthpiece. Conclusion: A flanged mouthpiece yields the largest values of VC in patients with bulbar and spinal ALS. Highlights: Deterioration of vital capacity (VC) in ALS signifies disease progression. Weak facial muscles consequent to ALS, with resulting poor mouth seal, interfere with VC measurement. VC measured with rigid cylindrical, flanged mouthpieces and oronasal mask. After one week, VC values recorded with a flanged mouthpieces were larger than baseline. Accurate VC measurement in ALS is best made with flanged mouthpiece.